Pelaksanaan Pembelajaran Huruf Hijaiyah Pada Anak Tunagrahita Di SLB C Muzdalifah - Noviar Panggabean; Zannatunnisya Zannatunnisya (Mathematics Education Study Program, 2025)
Children with intellectual disabilities are one of groups of children with mental disorders who have below average intellectual abilities and have limitations in thinking, low thinking skills, weak attention and memory In the process of learning the hijaiyah letters, children with intellectual disabilities find it difficult to recognize the hijaiyah letters, find it difficult to write the hijaiyah letters, are busy with their respective activities such as dancing, playing with their friends, some tend to be quiet because they lack enthusiasm in learning Therefore, interesting and interctive hijaiyah letter learning media are needed The use of learning media to teach the hijaiyah letters to mentally retarded students is very necessary However, the findings obtained in mentally retarded students who still cannot read the hijaiyah letters. This study aims to determine the role of learning media in learning the hijaiyah letters for mentally retarded students This study uses a descriptive qualitative approach with data collection techniques used are interviews and observations The results of the study show that learning media can stimulate students interest in learning and encourage them to be able to focus on the material The obstacles faced are the lack of concentration this is easily lost, high emotionality, and classes that are not yet adequate. The solution obtained is a firm attitude that teachers need to have as educators to provide motivation to students, and be patient in educating. With the existence of learning media, it can be one of the solutions in improving learning the hijaiyah letters in mentally retarded chidren.